Comparison between two gypsum content determination methods applied to the study of soils in arid regions - Youcef, Fouzia; Kairouani , Djihane; Boukarkar , Fatiha; Hamdi Aïssa , Baelhadj (Future Science, 2023)
With the scarcity, degradation of soils, the growing populations and the need to guarantee their food security, the valorization of gypsum soils widespread in arid and semi-arid regions is becoming a necessity. North African countries have a large part of their land area located in arid regions. It is therefore important to characterize the gypsum content using simple, rapid, economical and, environmentally friendly methods. Several methods have been proposed in the literature (chemical, thermogravimetric, and x-ray techniques). In this work, a comparison between two methods for gypsum determination in soils was undertaken. The first method of Coutinet is chemical and based on the use of BaSO4 for the precipitation of sulfate ions. The second method is Artieda method which is based on measuring the weight difference caused by the loss of crystalline water from gypsum molecules between the temperatures of 70 and 90 °C. To achieve the objective of this work, forty-three soil samples were analyzed. They were taken from two arid regions (Ouargla and Touggourt) located in the northern Sahara (Algeria). The soils contain gypsum accumulations. The results showed that most of the samples are slightly gypsiferous, with 36 and 32 samples for the Coutinet and Artieda methods respectively. A strong positive correlation (R2 = 0.95) exists between the results of the two methods studied. For gypsum contents higher than 2 %, the correlation coefficient is 0.94. However, for samples with contents less than 2 %, the correlation is very weak with R2=0.19. The Artieda method is thus encouraged for the gypsum quantification in soils of arid regions. This method is easy, requiring simple laboratory equipment (mainly a ventilated oven and a precision balance). Chemical methods have the disadvantage of being time-consuming and using expensive chemicals that are dangerous for the environment and human health.